Characteristics and variability of melon genotypes under shade conditions in greenhouse - Amalia Nurul Huda; Willy Bayuardi Suwarno (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2023)
The utilization of controlled greenhouses can be an alternative for melon (Cucumis melo L.) cultivation. Growing melon in greenhouses lowers the risk of pests and infections by diverse pathogens. Low solar irradiation during the rainy season and pollution in the greenhouse roof, may cause shade stress conditions for the plants inside. This study aimed to elucidate the plant and fruit characteristics of nine genotypes of melon grown under shade conditions in a greenhouse and the variability among them. The experiment was conducted in a greenhouse of Cikabayan Experimental Station, IPB University, Bogor, from November 2016 to January 2017. The genetic materials evaluated were nine melon genotypes from the Center for Tropical Fruit Studies at IPB University. A randomized complete block design with three replicates was followed. Shade intensity in the greenhouse was approximately 25%. The results showed that the genotype effect was significant for internode length, petiole length, plant height fruit, flesh thickness, fruit rind thickness, fruit weight, and total soluble solids. Genotype means for fruit weight were small in this experiment (< 300 g), whereas the total soluble solids were moderate to high (8.7-14.3 °Brix). Fruit diameter had a positive and significant correlation with leaf length, leaf width, and fruit length, whereas fruit weight had a positive and significant correlation with fruit diameter and fruit length. Keywords: correlation, honeydew, melon breeding, melon group, traits